Emerging Adults' Plans for Work and Family : a Freshman-Senior Comparison - Byrne, Brittany L.; Fuerstenberg, Eric; Camp, Sarah E.; Harris, Heather D.; Risdal, Megan; Ryan, Danielle; Ritchie, Laura; Miller, Stacy (My University, 2011)
Social constructionists have argued that sex differences in plans for combining work and family are a manifestation of societal pressures; under this logic, differences between men and women in work-family plans should be ameliorated by progression through four years of a liberal education that emphasizes gender egalitarianism. This study tests this idea.
Color poster with text and graphs.
Keywords: College students--Conduct of life--Sex differences; Posters; Families--Sex differences; Education, Higher--Social aspects--Surveys; Individual differences--Surveys; College students--Conduct of life--Surveys